The Impact of the Dominions of Mindfulness on the Organizational Innovation “Descriptive analytical study in some faculties of the University of Baghdad” - نوري, اسماء طه (Journal of Economics and Administrative Sciences, 2012)
Research seeks to test the impact of the dimensions of mindfulness on  organizational Innovation, proposed in the light of the review literature on two variables of the research, which referred in General to the dynamic relationship between them, as result of weakness of mindfulness as one important factor driving the diversity of innovation and time, ways to sustain and preserve and then support innovations made by creators, weakness in the overall level of organizational Innovation, this represents the problem research, data collection over designing   identification, distributed to sample Formed from (30) head Department at a number of colleges of the University of Baghdad, results confirms the validity of research hypotheses, which was notably a relationship link between mindfulness and organizational Innovation, as well as the positive impact of dimensions  of the first variable in the second one, depending on a number of those results we formulated a number of recommendations and conclusions aimed at reducing the size of the problem studied